Desain Game Edukasi Berbasis Android pada Materi Transformasi - Cut Eka Fitriana; Maimunah Maimunah; Yenita Roza (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this research is to produce a product in the form of media game android based education on transformation material. This research uses research and development (methodsR&D). with model procedure Four D (4-D). This research was conducted at one of the state junior high schools in Bengkalis Regency. The data collection technique was in the form of a questionnaire using a Likert scale. The data analysis technique was analyzed by transforming the average scale into qualitative sentences. Research.This results indesign in game adventure educational trans go an android-based accordance with the analysis of the needs and problems encountered at school. The results of the feasibility study show the validity of 86% with very valid criteria. In conclusion, products game android based education on transformation material are feasible and can be implemented in mathematics learning.